Roles, Obstacles, and Guidelines for Media to Combat Corruption - Pattanasrivichian, Suthida (King Prajadhipok’s Institute Journal, 2023)
Abstract This article presents barriers and guidelines for the media's role in the fight against corruption. The first part of the article is explained the overall obstacles especially in developing countries where corruption is the most problematic. The obstacles of the media to combat corruption consists of policy and legal, the right to access information, media ownership, professionalism and ethics of journalists, dangerous from harassments and the law, democracy and freedom of expression, and investigative journalism skills. According to the past research, opinions of academics and related stakeholders, there is a consensus that democracy, freedom of expression, funding, and investigative journalism is an important factor that will enable the media to play the preeminent role in anti-corruption. However, this article has arguments that the above factors do not improve the functioning of the media. Besides, countries where the media has freedom of expression the number of frauds did not decrease. This is caused from corruption news that are not professional, being intimidated by political and financial power, and also the changing situation of media business which the number of journalists has decreased and has to do many duties. Therefore, the investigative news, especially corruption news, has decreased. The content of the second part of the article, therefore, it presents guidelines for the media to report news on corruption in three main issues: 1) support the media’s economic independent, managements, and protecting journalists from intimidations, 2) developing news reporting skills in order to produce effective corruption news, and 3) improving access to information so that the media and people's sector can access information that will be a part of the audit process. In addition, there should be training and support in funding and knowledge to the people's sector, creating citizen journalists, and supporting independent media in monitoring, reporting corruption cases, and becomes a channel for the public to report clues about frauds.